Perceived Competence and Transition Experience of New Graduate Filipino Nurses - Nicolette Anne Ubas-Sumagasyay; Ryan Michael Flores Oducado (Fakultas Ilmu Keperawatan Universitas Indonesia, 2020)
Recruitment and hiring of new graduate nurses are seen as a potential strategy to mitigate the problem of nurse shortage. However, previous studies disclosed that new graduate nurses are inadequately prepared to enter practice and experience transition difficulties. This study aimed to determine the perceived competence and transition experience of new graduate Filipino nurses. Seventy-nine conveniently chosen new graduate nurses were surveyed in this descriptive cross-sectional research. Self-administered instruments were used to gather data. Descriptive statistics, Mann–Whitney U test, and Kruskal–Wallis test were the statistical tools employed. Results indicated that new graduate nurses had a high level of self-reported fundamental nursing skills (M= 7.99) and core competence (M= 8.16), although areas needing improvement were identified. There were no significant differences in the perceived competence based on the length of experience, year graduated, area of assignment, sex, type of school graduated, CPD participation, and hospital bed capacity (p> .05). The major difficulty experienced by new graduates during their transition was related to changes in role expectations (72.2%). Majority expressed the need for increased support during their transition (83.5%). The most satisfying aspects of their working environment were ongoing learning (81%) and peer support (74.7%), while the least satisfying was the negative nursing work environment (55.7%). New graduate nurses are equipped with the necessary nursing skills and core competencies. However, there are still gaps and areas needing improvement that should be addressed and supported to assist them in their transition to the world of professional nursing practice. Follow up, feedback, mentoring, and preceptorship are beneficial to enhance the competencies of new graduate nurses and facilitate their successful transition into the nursing workforce. Abstrak Persepsi Kompetensi dan Pengalaman Transisi Perawat Lulusan Baru Filipina. Rekrutmen dan perekrutan perawat lulusan baru dipandang sebagai strategi potensial untuk mengurangi masalah kekurangan perawat. Namun, penelitian sebelumnya mengungkapkan bahwa perawat lulusan baru tidak cukup siap untuk memasuki praktik dan mengalami kesulitan transisi. Penelitian ini bertujuan untuk menentukan persepsi kompetensi dan pengalaman transisi perawat lulusan baru Filipina. Tujuh puluh sembilan perawat lulusan baru yang dipilih dengan mudah disurvei dalam penelitian cross-sectional deskriptif ini. Instrumen yang dikelola sendiri digunakan untuk mengumpulkan data. Statistik deskriptif, uji Mann-Whitney U, dan uji Kruskal-Wallis adalah alat statistik yang digunakan. Hasil menunjukkan bahwa perawat lulusan baru memiliki tingkat tinggi keterampilan keperawatan fundamental yang dilaporkan sendiri (M= 7,99) dan kompetensi inti (M= 8,16), meskipun bidang yang perlu perbaikan diidentifikasi. Tidak ada perbedaan signifikan dalam kompetensi yang dirasakan berdasarkan lama pengalaman, tahun lulus, bidang tugas, jenis kelamin, jenis sekolah yang lulus, partisipasi CPD, dan kapasitas tempat tidur rumah sakit (p> 0,05). Kesulitan utama yang dialami oleh lulusan baru selama transisi mereka terkait dengan perubahan dalam ekspektasi peran (72,2%). Mayoritas menyatakan perlunya peningkatan dukungan selama masa transisi mereka (83,5%). Aspek yang paling memuaskan dari lingkungan kerja mereka adalah pembelajaran berkelanjutan (81%) dan dukungan sebaya (74,7%), sedangkan yang paling tidak memuaskan adalah lingkungan kerja keperawatan negatif (55,7%). Perawat lulusan baru dilengkapi dengan keterampilan keperawatan dan kompetensi inti yang diperlukan. Namun, masih ada kesenjangan dan bidang yang perlu diperbaiki yang harus ditangani dan didukung untuk membantu mereka dalam transisi mereka ke dunia praktik keperawatan profesional. Tindak lanjut, umpan balik, pendampingan, dan pelatihan guru bermanfaat untuk meningkatkan kompetensi perawat lulusan baru dan memfasilitasi keberhasilan transisi mereka menjadi tenaga kerja keperawatan. Kata Kunci: keterampilan keperawatan, pengalaman transisi, penilaian kompetensi, perawat lulusan baru